Designing for ethical innovation: A case study on ELSI co-design in emergency. Issue 95 (November 2016) - Liegl, Michael; Boden, Alexander; Büscher, Monika; Oliphant, Rachel; Kerasidou, Xaroula
Abstract: The ever more pervasive 'informationalization' of crisis management and response brings both unprecedented opportunities and challenges. Recent years have seen the emergence of attention to ethical, legal and social issues (ELSI) in the field of Information and Communication Technology. However, disclosing (and addressing) ELSI issues in design is still a challenge because they are inherently relational, arising from interactions between people, the material and design of the artifact, and the context. In this article, we discuss approaches for addressing such 'deeper' and 'wider' political implications, values and ethical, legal and social implications that arise between practices, people and technology. Based on a case study from the BRIDGE project, which has provided the opportunity for deep engagement with these issues through the concrete exploration and experimentation with technologically augmented practices of emergency response, we present insights from our interdisciplinary work aiming to make design and innovation projects ELSI-aware. Crucially, we have seen in our study a need for a shift from privacy by design towards designing for privacy, collaboration, trust, accessibility, ownership, transparency etc., acknowledging that these are emergent practices that we cannot control by design, but rather that we can help to design for— calling for approaches that allow to make ELSI issues explicit and addressable in design-time. Highlights: Problematises regulatory approaches like Privacy Impact Assessment and Privacy by Design as forms of 'solutionism'. Claims that ethical implications of emergency IT systems unfold in use. Caution against ethics checklists in IT innovation for emergency collaboration. Design for Emergency IT Systems needs to be collaborative design. Discussing design approaches for radically careful design of IT systems for domain of emergency response.